Air tamponade of the heart - Gołota, Janusz J.; Orłowski, Tadeusz; Iwanowicz, Katarzyna; Snarska, Jadwiga (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Pneumopericardium is a rare disease defined as the presence of air or gas in the pericardial sac. Among the etiological factors, the following stand out: chest trauma, barotrauma, air-containing fistulas between the pericardium and the surrounding structures, secondary gas production by microorganisms growing in the pericardial sac, and iatrogenic factors. Until now, spontaneous pneumopericardium has been considered a harmless and temporary state, but a review of clinical cases indicates that the presence of air in the pericardium can lead to cardiac tamponade and life-threatening hemodynamic disturbances. We present the case of an 80-year-old patient with a chronic bronchopericardial fistula, who suffered from a cardiac arrest due to air tamponade of the heart.